Cooperation networks in the tourism sector: multiplication of business opportunities - Mendonça, Vítor (2015)
Inter-organizational strategic alliances, in which networks of cooperation stand out, have proved to be a good model to provide more competitive organizations. However, there are still shortcomings concerning models and supporting technologies that help the creation of inter-organizational arrangements. This paper presents a conceptual model for the establishment of cooperation networks, an information system that supports the proposed model and, finally, the results of a case study in the tourism sector. (C) 2015 Published by Elsevier B.V.